2015
DOI: 10.18632/oncotarget.4099
|View full text |Cite
|
Sign up to set email alerts
|

Ebselen inhibits QSOX1 enzymatic activity and suppresses invasion of pancreatic and renal cancer cell lines

Abstract: Quiescin sulfhydryl oxidase 1 (QSOX1) is a highly conserved disulfide bond-generating enzyme that is overexpressed in diverse tumor types. Its enzymatic activity promotes the growth and invasion of tumor cells and alters extracellular matrix composition. In a nude mouse-human tumor xenograft model, tumors containing shRNA for QSOX1 grew significantly more slowly than controls, suggesting that QSOX1 supports a proliferative phenotype in vivo. High throughput screening experiments identified ebselen as an in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 35 publications
2
44
0
Order By: Relevance
“…Furthermore, QSOX 1 expression levels seem to be correlated with patient prognosis in breast cancer . As such, QSOX 1 is an emerging target in tumor biology and recent reports indicate that invasion of cancer cells can be suppressed by inhibiting its enzymatic activity .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, QSOX 1 expression levels seem to be correlated with patient prognosis in breast cancer . As such, QSOX 1 is an emerging target in tumor biology and recent reports indicate that invasion of cancer cells can be suppressed by inhibiting its enzymatic activity .…”
Section: Discussionmentioning
confidence: 99%
“…Ebselen is a low-molecular-weight organoselenium drug that shows pleiotropic mode of action and due to its very low toxicity there are no barriers to using it in humans [15]. It is a well-known agent with therapeutic activity in neurological disorders [16] and cancers [17]. It also showed an antiviral effect on neurotropic viruses [18] and hepatitis C virus [19].…”
Section: Introductionmentioning
confidence: 99%
“…QSOX1 promotes the growth and invasion of caner cells and influences extracellular matrix composition. Hanavan et al [21] had report that, after mass spectrometric analysis of ebselentreated QSOX1, they found that the C165 and C237 of QSOX1 covalently bound to ebselen. Their study depicts the anti-neoplastic properties of ebselen in renal cancer cell lines, providing a "proof-of-principle" that enzymatic inhibitorry of QSOX1 may have clinical benefits.…”
Section: Ebselenmentioning
confidence: 99%